Prevalence and Pattern of Substance Abuse among 18 to 60 years Male in a Rural Area of District Etawah, Uttar Pradesh - Mehra, Jyoti; Nayak, Kripashankar; Kharya, Pradip; Krishnappa, Kiran Krishnappa; Jain, Pankaj Kumar; Gangwar, Abhinav (Indian Journal of Community Health, 2022)
Abstract: Adolescent and young people’s behavior is of major concern due to Substance abuse. According to WHO, Substance abuse is consistently or sporadic drug use inconsistent with or unrelated to acceptable medical practice. Globally, alcohol and tobacco as a risk factors cause 4.0% and 4.1% of the overall burden of disability respectively. Objective: To determine the prevalence of substance abuse among 18 to 60 years’ male in rural Etawah and to identify type and pattern of substance abuse. Material and Methods: It was a community based cross sectional study carried out in five block of district Etawah for a period of one and half year. 1500 participants were interviewed using pre designed pre-tested questionnaire and data regarding socio demographic profile and pattern of abuse were collected. Data was entered in Microsoft excel sheet and analyzed by SPSS version 24 using appropriate statistical test. Result: Among 1500 participants, majority were below 30 years of age (i.e. 42.8%). In this study prevalence of Substance use among was 47% [707/1500]. Among all the other substance use, smokeless tobacco showed highest prevalence. Conclusion: Substance use is common in both urban as well as in rural area. So there is a need to educate and aware people regarding bad effects of drug abuse.